AN ANALYSIS ENGLISH LANGUAGE STUDENTS DIFFICULT IN WRITING POETRY BASED ON PERSONAL EXPERIENCE - Wulandari, Imei; Nazha, Mildani Ulpa; Kasih, Nurwidia; Damanik, Bella Angelina; Sianturi, Tessalonika TNS; Damanik, Tita Princesva (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This study analyzes the difficulties faced by English language students in writing poetry based on personal experience. Writing poetry is a complex skill that requires linguistic competence, creativity, and the ability to convey emotions and imagery effectively. Using a qualitative research design, data were collected through questionnaires and semi-structured interviews with students of the English Education Department who had prior experience in writing poetry. The study aimed to identify the primary challenges students encounter, the contributing factors, and how these difficulties manifest in their written outputs. The findings reveal that while most students show moderate to high interest in poetry writing, they face significant challenges, including limited vocabulary, insufficient understanding of figurative language and poetic devices, difficulties in organizing poem structure, and cognitive challenges in transforming personal experiences into expressive and artistic forms. Affective factors such as low creative confidence and uncertainty in selecting meaningful personal experiences further exacerbate these difficulties. The study highlights the need for structured instructional support, including explicit teaching of literary devices, guided pre-writing exercises, and opportunities for reflective feedback to enhance students? poetry writing skills. These insights contribute to understanding the intersection of personal experience and creative writing, offering practical implications for educators, curriculum developers, and researchers seeking to improve poetry instruction in language classrooms.Keywords: poetry writing, personal experience, writing difficulties, EFL students, creative expression